Effects of different tidal inlet configurations on the water quality of an estuary lagoon complex in northeastern Brazil - Luz,Teresa Elane Bezerra (2022)
ABSTRACT The Mundaú-Manguaba Estuary Lagoon Complex (CELMM), located on the coast of Alagoas state in Northeastern Brazil, consists of two choked coastal lagoons connected to the Atlantic Ocean by a series of narrow channels, establishing a single tidal inlet, which dynamically alters their position. This study uses the modeling system SisBaHiA® (in Portuguese, Sistema Hidrodinâmico Ambiental) and Trophic Index (TRIX) to evaluate how morphological changes in the CELMM can influence the water quality of the lagoons. The results showed that water quality is mainly influenced by river discharge regimes, with no major changes in the region of the tidal inlet for the three simulated years (2006, 2014 and 2017). Trophic index showed greater changes in the rainy season, with a decline in values as river discharge increases, mainly in the northwest and central portions of the Mundaú Lagoon. In the Manguaba Lagoon an opposite pattern was found, namely a rise in the Trophic index with increased river discharges.